PENGARUH PERBEDAAN KONSENTRASI HCl DAN WAKTU DEMINERALISASI TERHADAP SIFAT FISIK GEL GELATIN TULANG CEKER AYAM - Fina Choirunnisa; Widyasari Putranti (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2018)
The effect of HCl concentration and demineralization time on physical properties of gelatinous chicken bone was done to see the effect of different HCl concentration used as catalyst and demineralization time to rendemen, pH, viscosity, moisture content, and ash content of gelatin generated. This study used a complete randomized design (RAL) with two factors: variation of HCl concentration (0.05N, 0.15N and 0.25N) and demineralization time variation (12 hours and 24 hours). Chicken bone gelatin gel is obtained by hydrolyzing chickens that have been demineralized with acid solution. The result of the hydrolysis is dried to produce dry gelatin which will be tested its physical properties. The results of this study indicate that the difference of HCl concentration and demineralization time have an effect on the rendemen, viscosity, and gelatin water content produced. Different concentrations of HCl and demineralization time did not affect the pH and the resulting gelatin ash content.